2014
DOI: 10.3126/ajms.v6i3.11361
|View full text |Cite
|
Sign up to set email alerts
|

In vivo antiplasmodial activities of Nauclea latifolia

Abstract: Background:The plant Nauclea latifolia is widely used in the southern parts of Nigeria for the treatment of malaria. Malaria is the number one killer disease in Nigeria. WHO reports that malaria continues to cause approximately 207 million cases of infection around the world and kills yearly about 627,000 people. It still kills a child somewhere in the world every minute. The study was aimed at evaluating the in vivo antiplasmodial activities of the extract and fractions (n-hexane, chloroform, ethyl acetate, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…N. subdita contains secondary metabolites such as tannins, alkaloids, and phenolic compounds, which act as a natural bactericide [26]. The leaves, bark, and root of Nauclea latifolia, N. subdita, and Nauclea officinalis are also known to contain alkaloids, flavonoids, and tannins [27][28][29].…”
Section: Histopathological Changes On Liver and Kidneymentioning
confidence: 99%
“…N. subdita contains secondary metabolites such as tannins, alkaloids, and phenolic compounds, which act as a natural bactericide [26]. The leaves, bark, and root of Nauclea latifolia, N. subdita, and Nauclea officinalis are also known to contain alkaloids, flavonoids, and tannins [27][28][29].…”
Section: Histopathological Changes On Liver and Kidneymentioning
confidence: 99%
“…Based on their traditional uses against malaria N. latifolia and N. pobeguinii have been evaluated as antiplasmodial (Table 14). The first report of antimalarial activity of N. latifolia stem and roots aqueous extracts on Plasmodium falciparum was published in 1998 by Benoit-Vical et al This activity was later confirmed by other studies using aqueous, alcoholic or hydroalcoholic extracts of stem bark, roots or leaves (Udobre et al, 2013a;Zirihi et al, 2005;Ettebong et al, 2014;Onyesom et al, 2015;Dibua et al, 2013;Adebajo et al, 2014; for a review see Boucherle et al, 2016). Hydro-alcoholic extracts of N. pobeguinii stem bark also presented antiplasmodial activity.…”
Section: Anti-parasitementioning
confidence: 87%
“…Care was taken not to overlap fields. The parasite density was calculated using the formula (27): Repository/prophylactic activity The method of Ettebong et al (28) was also employed to evaluate the prophylactic activity of the extract. Groups 1-3 were administered with 320, 640 and 960 mg/kg of the extract orally.…”
Section: Determination Of Antiplasmodial Activities Suppressive Activitymentioning
confidence: 99%
“…The earlier method described by Ettebong et al, (28) and Adu-Gyasi et al, (26) was used. A quantity of 0.2 ml of blood containing P. berghei berghei parasitized blood was administered intraperitoneally to the mice on the first day (D0) and left for 72 hours for parasitaemia to be established.…”
Section: Curative Activitymentioning
confidence: 99%